2021
DOI: 10.1200/jco.20.02712
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Safety, and Correlative Biomarkers of Toripalimab in Previously Treated Recurrent or Metastatic Nasopharyngeal Carcinoma: A Phase II Clinical Trial (POLARIS-02)

Abstract: PURPOSE As yet, no checkpoint inhibitor has been approved to treat nasopharyngeal carcinoma (NPC). This study was aimed to evaluate the antitumor activity, safety, and biomarkers of toripalimab, a new programmed death-1 (PD-1) inhibitor for recurrent or metastatic NPC (RM-NPC) refractory to standard chemotherapy. PATIENTS AND METHODS In this single-arm, multicenter phase II study, patients with RM-NPC received 3 mg/kg toripalimab once every 2 weeks via intravenous infusion until confirmed disease progression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
234
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 206 publications
(249 citation statements)
references
References 43 publications
14
234
1
Order By: Relevance
“…1B). Consistent with previous studies, TP53 was the most significantly mutated gene (n = 10; q = 1.1 × 10 −6 ), followed by TRAF3, NFKBIA, AEBP1, and NLRC5; all of which have been reported to regulate NF-κB signaling 4,[8][9][10][11][12][13][14]17 . In addition, significant somatic aberrations detected in HLA-A and NLRC5 suggest impairment of antigen presentation while PTEN mutations may activate the PI3K pathway [8][9][10] .…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…1B). Consistent with previous studies, TP53 was the most significantly mutated gene (n = 10; q = 1.1 × 10 −6 ), followed by TRAF3, NFKBIA, AEBP1, and NLRC5; all of which have been reported to regulate NF-κB signaling 4,[8][9][10][11][12][13][14]17 . In addition, significant somatic aberrations detected in HLA-A and NLRC5 suggest impairment of antigen presentation while PTEN mutations may activate the PI3K pathway [8][9][10] .…”
Section: Resultssupporting
confidence: 89%
“…Notably, a single recurrent mutation (chr2:10097565 C > T) was identified in four tumors from three patients (Supplementary figure 2). Despite reports from several genome sequencing studies conducted thus far, this represents the first recurrent mutation identified in the non-coding region of NPC genome [8][9][10][11][12][13][14] . Furthermore, this mutation results in a gain of a putative NFKB1/p50 binding sequence upstream of RRM2 which has been reported to be associated with NF-κB-signaling activation 18 .…”
Section: Resultsmentioning
confidence: 85%
See 3 more Smart Citations